Efeito in vitro de produtos homeopáticos sobre fungos entomopatogênicos Beauveria Bassiana (Bals.) Vuill. e Metarhizium Anisopliae (Metsch.) Sorok. - Damin, Silvana (2013)
The increasing use of natural agricultural pesticides and the need of real proof of the effects of these products on entomopathogens are the basis of this study, which aimed to assess the in vitro effect of the following homeopathic products: Arsenicum album 24CH; Calcareous carbonica 30CH; Kali iodatum 100CH; Phosphorus 3CH; Silicea 30CH; Staphysagria 06, 30, and 100CH; Spodoptera frugiperda 30CH; Sulphur 100 and 200CH; and Thuya occidentalis 200CH (applied at a concentration of 0.1% of sterile distilled homeopathic/water) on the fungi Beauveria bassiana and Metarhizium anisopliae. The treatments were sprayed on the fungi in the PDA culture media in Petri or Rodac-type dishes, where conidia viability, colony-forming units (CFU), vegetative growth, and production of conidia were assessed. Homeopathic treatments were also assessed regarding the insecticide activity of these fungi against Diatraea saccharalis caterpillars. In tests with the fungus B. bassiana (Chapter 1) treatments Phosphorus 3CH; Silicea 30CH; Staphysagria 30CH and Spodoptera frugiperda 30CH reduced viability. All treatments except Arsenicum album 24CH promoted increased CFU. Likewise, Phosphorus 3CH; Staphysagria 30CH; Staphysagria 100CH and Sulphur 200CH promoted increased vegetative growth. In tests with the fungus M. anisopliae (Chapter 2), the treatments did not affect negatively the viability, vegetative growth and conidial production. All treatments were compatible to the fungus B. bassiana and M. anisopliae. Generally the insecticidal activity of fungi B. bassiana and M. anisopliae on D. saccharalis, was not influenced by the treatments, however, the drug Thuya occidentalis 200CH reduced activity B. bassiana on the insect